Incipient sensor fault estimation and accommodation for inverter devices in electric railway traction systems. (26th September 2016) - Zhang, Kangkang; Jiang, Bin; Yan, Xing‐Gang; Mao, Zehui
Summary: This paper proposes an incipient sensor fault estimation and accommodation method for three‐phase PWM inverter devices in electric railway traction systems. First, the dynamics of inverters and incipient voltage sensor faults are modeled. Then, for the augmented system formed by original inverter system and incipient sensor faults, an optimal adaptive unknown input observer is proposed to estimate the inverter voltages, currents and the incipient sensor faults. The designed observer guarantees that the estimation errors converge to the minimal invariant ellipsoid. Moreover, based on the output regulator via internal model principle, the fault accommodation controller is proposed to ensure that the v o d and v o q voltages track the desired reference voltages with the tracking error converging to the minimal invariant ellipsoid. Finally, simulations based on the traction system in CRH2 (China Railway High‐speed) are presented to verify the effectiveness of the proposed method. Copyright © 2016 John Wiley & Sons, Ltd.